The position of contemporary orientalism towards Islamic theology (the Mu’tazila sect as a model): Analytical and comparative study of selected models of contemporary orientalists. (Henery Corbin, Harry Austryn Wolfson, W. Montgomery Watt) - Saloomi, Hala Kadhim (Al-Adab Journal, 2021)
The science of Islamic theology, including the Mu’tazila group, has occupied a great interest among orientalists since they got acquainted with Islamic thought, and today with contemporary Orientalism we find that interest tends to increase in an attempt to get rid of the previous sayings that most framed the Western meta-ideology, to reveal anew the most important external, cultural and social influences More precisely about the subjective content of Islamic theology, and we will see that this new treatment of speech synthesis, It does not constitute any departure from the path of their predecessors from the Orientalists, as they kept the same methodology of influence and influence, and the hypothetical deductive method, or the method of guesswork and so on. Those sayings that were installed in several molds and formulas can be truly considered an extension of their predecessor. Consequently, they could not dispense with what the old Orientalism echoed.